The main factors that affect on prospects of unconventional gas extractional in Ukraine - Метошоп, І. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Preconditions and potential of the mining of unconventional gas in Ukraine, established the basic stimulating and inhibiting factors influencing on the perspective of the extraction of shale gas as well as outlined a number of matters, to which the solutions are the main priority in order to reconcile the interests of all stakeholders